DEVELOPMENT OF ECONOMIC THINKING IN THE YOUNGER GENERATION - Babaeva Sabinabonu Davronbek qizi (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: The article analyzes the economic thinking of young people, its significance and ways of formation in the modern world. It examines key factors influencing the development of economic knowledge among youth, including education, family traditions, accessibility of information technologies, and globalization. Special attention is paid to financial literacy for successful social adaptation, as well as challenges young people face such as lack of experience, consumer culture, and psychological barriers. The article suggests solutions through educational programs, mentorship, and promotion of financial self-education.